Rewarding Creativity: The Moderating Role of Personality - Maryam Rassouli-Baghi (Junior Management Science (JUMS), 2024)
The aim of this paper is to find out if Openness to Experience and Extraversion have an interacting effect on the relationship between monetary rewards and originality. Therefore, in an online experiment which was set up in two parts - the first part measured participants personality level whereas the second part included a divergent thinking task, where the originality of ideas was measured - I find that Openness to Experience and Extraversion positively influence creativity. Further, it is as- sumed, that monetary rewards positively influence an individual's creativity, as those individuals being rewarded for creativity performed more creative. However, analysis indicates that there is no interaction effect as assumed. As the ability of creative thinking is essential for companies and can even lead to a competitive advantage, the findings of this study provide useful insights about the relevance of personality on creativity for theory and practice.
Keywords: 650; creativity; divergent thinking; performance; personality; reward sensitivity